Evidence for a conserved microbiota across the different developmental stages of Plodia interpunctella. (18th December 2017) - Mereghetti, Valeria; Chouaia, Bessem; Limonta, Lidia; Locatelli, Daria Patrizia; Montagna, Matteo
Abstract: Diversity and composition of lepidopteran microbiotas are poorly investigated, especially across the different developmental stages. To improve this knowledge, we characterize the microbiota among different developmental stages of the Indian meal moth, Plodia interpunctella, which is considered one of the major pest of commodities worldwide. Using culture‐independent approach based on Illumina 16S rRNA gene sequencing we characterized the microbiota of four developmental stages: eggs, first‐, and last‐instar larvae, and adult. A total of 1022 bacterial OTUs were obtained, showing a quite diversified microbiota associated to all the analyzed stages. The microbiotas associated with P. interpunctella resulted almost constant throughout the developmental stages, with approximately 77% of bacterial OTUs belonging to the phylum of Proteobacteria. The dominant bacterial genus is represented by Burkholderia ( ∼ 64%), followed by Propionibacterium, Delftia, Pseudomonas, and Stenotrophomonas . A core bacterial community, composed of 139 OTUs, was detected in all the developmental stages, among which 112 OTUs were assigned to the genus Burkholderia . A phylogenetic reconstruction, based on the 16S rRNA, revealed that our Burkholderia OTUs clustered with Burkholderia cepacia complex, in the same group of those isolated from the hemipterans Gossyparia spuria and Acanthococcus aceris . The functional profiling, predicted on the base of the bacterial 16S rRNA, indicates differences in the metabolic pathways related to metabolism of amino acids between preimaginal and adult stages. We can hypothesize that bacteria may support the insect host during preimaginal stages.